Absence of Varicella-zoster Virus (VZV) Glycoprotein V Does not Alter Growth of VZV in vitro or Sensitivity to Heparin - Cohen, Jeffrey I.; Seidel, Karen E. (Journal of General Virology, 1994)
Varicella-zoster virus (VZV) encodes at least five glycoproteins, gpl to gpV. VZV gpV, M r 100K to 110K, is the product of VZV open reading frame (ORF) 14. VZV gpV is homologous to herpes simplex virus gC and pseudorabies virus gill. To determine whether gpV is required for viral replication, we inserted a stop codon after the fifteenth codon of the ORF 14 gene in a cosmid containing the gene. Transfection of human melanoma cells with the cosmid containing the mutant ORF14 gene and three other cosmids resulted in the production of infectious VZV. Immunoprecipitation indicated that the mutant virus did not express gpV. VZV that did not express gpV grew at the same rate as parental virus and was inhibited by heparin to a similar extent. The pattern of inhibition by heparin of the gpV mutant was similar to that reported for a herpes simplex virus mutant that does not contain gC, but different from that described for a pseudorabies virus mutant devoid of gill. These results indicate that VZV gpV is not required for viral replication in vitro.